Redshift and luminosity evolution of the intrinsic alignments of galaxies in Horizon-AGN - Chisari, N; Laigle, C; Codis, S; Dubois, Y; Devriendt, J; Miller, L; Benabed, K; Slyz, A; Gavazzi, R; Pichon, C (Oxford University Press, 2016)
Intrinsic galaxy shape and angular momentum alignments can arise in cosmological large-scale structure due to tidal interactions or galaxy formation processes. Cosmological hydrodynamical simulations have recently come of age as a tool to study these alignments and their contamination to weak gravitational lensing. We probe the redshift and luminosity evolution of intrinsic alignments in Horizon-AGN between z=0 and z=3 for galaxies with an r-band absolute magnitude of <-20. Alignments transition from being radial at low redshifts and high luminosities, dominated by the contribution of ellipticals, to being tangential at high redshift and low luminosities, where discs dominate the signal. This cannot be explained by the evolution of the fraction of ellipticals and discs alone: intrinsic evolution in the amplitude of alignments is necessary. The alignment amplitude of elliptical galaxies alone is smaller in amplitude by a factor of ~2, but has similar luminosity and redshift evolution as in current observations and in the nonlinear tidal alignment model at projected separations of > 1 Mpc. Alignments of discs are null in projection and consistent with current low redshift observations. The combination of the two populations yields an overall amplitude a factor of ~4 lower than observed alignments of luminous red galaxies with a steeper luminosity dependence. The restriction on accurate galaxy shapes implies that the galaxy population in the simulation is complete only to an r-band absolute magnitude of <-20. Higher resolution simulations will be necessary to avoid extrapolation of the intrinsic alignment predictions to the range of luminosities probed by future surveys.